(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article examines the potential of green sukuk as a tool for financing sustainable development in Uzbekistan. It analyzes the country’s economic and financial context, the current state of Islamic finance and the sukuk market, and the conceptual framework of green sukuk. The article also identifies the opportunities and challenges associated with the implementation of this instrument. The study proposes strategies and practical recommendations for introducing green sukuk, including the development of a regulatory framework. The proposed measures are intended to facilitate the successful issuance of the first green sukuk in Uzbekistan and to unlock their potential in supporting the country’s transition to a green economy.